Uso y manejo de las tecnologías de la información y comunicación en el proceso de enseñanza aprendizaje de los estudiantes del décimo año de educación básica de la escuela Remigio Romero y Cordero del cantón Ventanas, periodo lectivo 2021-2022 - Burgos Zamora, Kerly Johanna (2023)
The present research work synthesizes the results and implementation of an educational plan for the acquisition of the use of ICT in the teachers of the Remigio Romero y Cordero School of Basic Education of the Chacarita parish, of the Ventanas canton, Province of Los Ríos. Taking into account that education is currently going through a transformation in active methodologies that promote the acquisition of new skills in training models, a training plan in ICT skills for teachers is described, a process that allows teachers to acquire tools basic to capture in its teaching-learning transformation the dynamism and motivational aspect that technologies mark, approaching the world where current students are immersed, developing relevance with the environment that surrounds us. At the same time, teachers will discover tools that provide various functions that focus on supporting the planning, organization and evaluation process that they must carry out during their pedagogical work.